A very rare complication of subacute pericarditis: a case report of spontaneous coronary artery rupture. Issue 12 (30th November 2021) - Fujimoto, Tomotaka; Yanishi, Kenji; Zen, Kan; Matoba, Satoaki
Abstract: Background: Spontaneous coronary artery rupture (SCAR) is an extremely rare and highly lethal disease. Case summary: A 74-year-old man who had undergone respiratory surgery (robot-assisted thoracoscopic surgery) presented with exertional dyspnoea since postoperative day (POD) 6. Echocardiography and contrast-enhanced computed tomography showed diffuse pericardial effusion, and a 12-lead electrocardiogram showed widespread concave ST-segment elevation. The diagnosis of acute pericarditis was made based on the absence of significant elevation of cardiac enzymes and the presence of elevated C-reactive peptide levels. The patient was started on anti-inflammatory medication, including steroids; however, on POD 11, the patient developed a sudden cardiopulmonary arrest due to cardiac tamponade. Extracorporeal cardiopulmonary resuscitation was performed, and an emergency coronary angiography showed contrast extravasation from the left anterior descending artery to the epicardium. He was diagnosed with SCAR and underwent transcatheter arterial embolization (TAE) and pericardial drainage. Discussion: In this case, SCAR occurred during the course of acute pericarditis. We speculated that the cause of SCAR was more affected with pericarditis than injury by the respiratory surgery. The clinical course of acute pericarditis generally has a good prognosis, but the rare occurrence of fatal complications should be considered, suggesting the need for careful follow-up. In addition, TAE was a less invasive and feasible treatment for SCAR.